2009
DOI: 10.1093/nar/gkp901
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of replication structures at the nanometer scale using super-resolution light microscopy

Abstract: DNA replication, similar to other cellular processes, occurs within dynamic macromolecular structures. Any comprehensive understanding ultimately requires quantitative data to establish and test models of genome duplication. We used two different super-resolution light microscopy techniques to directly measure and compare the size and numbers of replication foci in mammalian cells. This analysis showed that replication foci vary in size from 210 nm down to 40 nm. Remarkably, spatially modulated illumination (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 32 publications
7
71
0
Order By: Relevance
“…In addition, STED microscopy has been shown to be useful for neurobiology in the study of synaptic connections between nerve cells [Willig et al 2006;Nagerl et al 2008]. Structured illumination microscopy approaches are presently used for a similar range of applications [Martin et al 2004;Hildenbrand et al 2005;Birk et al 2007;Schermelleh et al 2008;Reymann et al 2008;Baddeley et al 2010b;Markakis et al 2010]; in addition, they have been shown to allow an improved imaging quality of retina tissue, e.g. to analyze age dependent macula degeneration Ach et al 2012].…”
Section: Impact Of Enhanced Resolution Light Microscopy In the Bioscimentioning
confidence: 99%
“…In addition, STED microscopy has been shown to be useful for neurobiology in the study of synaptic connections between nerve cells [Willig et al 2006;Nagerl et al 2008]. Structured illumination microscopy approaches are presently used for a similar range of applications [Martin et al 2004;Hildenbrand et al 2005;Birk et al 2007;Schermelleh et al 2008;Reymann et al 2008;Baddeley et al 2010b;Markakis et al 2010]; in addition, they have been shown to allow an improved imaging quality of retina tissue, e.g. to analyze age dependent macula degeneration Ach et al 2012].…”
Section: Impact Of Enhanced Resolution Light Microscopy In the Bioscimentioning
confidence: 99%
“…Furthermore, although some previous superresolution studies have been able to probe subnuclear structures in mammalian cells (24,25), they have not provided absolute quantification in molecular copy numbers. Aside from less-than-complete labeling of molecular species, the difficulty stems primarily from the fact that the blinking photophysics of a dye results in multiple detection events for the same molecule over the course of image acquisition.…”
Section: Significancementioning
confidence: 99%
“…However, recent experiments using super-resolution light microscopy indicate that replication factories rather than being distinct structures might better be considered as nuclear domains with specific functional roles. Hence, the 1200 factories typically seen in diploid mammalian cells using confocal microscopy (Ma et al 1998;Cseresnyes et al 2009) could be resolved into 2-3 times more active sites using super-resolution systems (Cseresnyes et al 2009;Baddeley et al 2010). …”
Section: Visualizing Replication In the Nucleusmentioning
confidence: 99%